2012
DOI: 10.1111/j.1524-4725.2011.02171.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clinical Response in Patients with Vitiligo Undergoing Autologous Epidermal Punch Grafting

Abstract: Punch grafting is successful in most patients with vitiligo, with an 87% graft survival rate, but the rates of repigmentation vary depending on clinical characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…However, cobblestone appearance occurred as an adverse effect in 30% of the patients. In contrast, Babu et al [15] and Feetham et al [16] performed 1.5-mm minigrafting in 8 and 30 patients, respectively, and they did not report any significant adverse effects, such as cobblestone appearance. Kato et al [9] have recently reported the results of their performance of the safer 1-mm minigrafting procedure in 20 patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, cobblestone appearance occurred as an adverse effect in 30% of the patients. In contrast, Babu et al [15] and Feetham et al [16] performed 1.5-mm minigrafting in 8 and 30 patients, respectively, and they did not report any significant adverse effects, such as cobblestone appearance. Kato et al [9] have recently reported the results of their performance of the safer 1-mm minigrafting procedure in 20 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Papers on application of surgical procedures to treat vitiligo and/or their improvement dominated over investigation of other treatment modalities, counting for nearly a half (38 of 78) papers published in a field of clinical vitiligo management since January 2010 until May 2012. The reports could be stratified as focused on continuing evaluation of efficiency of various surgical methods per se (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), including retrospective studies of large patient cohorts (13,18), improvement of existing treatments through advancement in methodology (18)(19)(20)(21)(22)(23)(24)(25), or by combining with other nonsurgical treatments (26)(27)(28)(29)(30)(31)(32)(33), development and evaluation of novel surgical techniques in vitiligo treatment (34)(35)(36)(37), and extending treatments on a novel patient groups (38)(39)(40)(41), mostly children and adolescents (38)(39)(40).…”
Section: Surgical Methodsmentioning
confidence: 99%
“…44 Similarly, the lower number of cells counted in samples collected over the knee is in line to the poorer response reported in the literature at joint sites. 45 Based on the possible stimulation of melanocytes induced by growth factors and mediators released in response to the graft trauma, it can be hypothesized that the activation of the microenvironment can be better promoted by a higher number of smaller punch grafts compared to a minor number of bigger punches, thus resulting in a more effective clinical outcome. Moreover, the reduced number of melanocytes observed in the samples collected from patients subjected to bigger size punch graft and presenting cobble stoning may be ascribed to the unfavourable microenvironment for melanocyte migration created by the fibrotic reaction of this side-effect.…”
mentioning
confidence: 99%